ANALOG IR-PHOTOMETER - Pereversentsev, A. F.; Ivanov, V. N.; Ryabov, A. V.; Arkhipov, M. G.; Lisova, L. E. (Одеські астрономічні публікації, 2017)
The circuit design is described of a photometer functioning in the analog regime with the signal accumulation and conversion and its input into the computer.